Kinetic study of ZnFe2O4 formation from mechanochemically activated Zn-Fe2O3 mixtures - Botta, Pablo Martín (2006)
The kinetics of ZnFe2O4 formation starting from mechanochemically activated Zn-Fe2O3 powders are studied. Mixtures of metallic Zn and hematite were activated under air atmosphere in a high energy mill and thermally treated at temperatures between 500 and 650 °C during several holding times. During the activation, morphological and compositional changes were observed, but ZnFe2O4 formation was not detected. The ZnFe2O4 content in heated samples was determined using quantitative X-ray diffraction analysis. The resulting conversion-time curves were fitted using different kinetic models of solid-state reaction, calculating the kinetic parameters of the studied reaction. The comparison with the conventional synthesis method revealed that the mechanochemical treatment provoked a change of the rate-controlling step and a significant decrease of the activation energy, which was more evident for the more activated mixtures.